Cytological and clinical staging of transmissible venereal tumour at the Veterinary Hospital of Botucatu - Flórez, Luis Mauricio Montoya; Ordóñez, Francisco Pedraza; Monteiro, Sharlenne [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2013)
The canine transmissible venereal tumour is a transplantable neoplasm of great scientific interest for its versatile biological behaviour and its complex mechanisms of evolution. The main objective of this research was to obtain information in order to carry out a better clinical and therapeutic approachof patients with this tumour, twenty dogs with clinical and cytological diagnosis of TVT were studied. Theclinical staging (TNM) was carried out, thecytomorphologicclassification and the nuclear malignancyand cytoplasmic criteria were obtained. TheChi-square test and the Mann-Whitney test were used for data analysis. Eighteen animals were mixed race with a 2 to 10 range of age, and the main location of the tumor was the external genital and the predominant cellular type was plasmacytoid. Themalignancynuclear and cytoplasmic criteria,with the exception of the perinuclear halo,were similar to those described in the literature. During the RNM classification, two tumours were categorized as T3M and one as T3N1; the other tumours were classified in different T degrees. Despite the lack of statistical significance for the employed method, in general, a good clinical relationship was seen between TNM staging and cytopathological findings, suggesting that both provide greater certainty about the degree of aggressiveness, progression and prognosis in the patients with TVT, as it occurs in other typesof tumours. Use of staging in this tumour can serve as a criterion to suggest the possible evolution and type of therapy.Nevertheless we recommend future research to help define the benefits of using the TNM clinical staging in TVT.

El tumor venéreo transmisible canino es una neoplasia trasplantable que despierta gran interés científico por su comportamiento biológico versátil y sus complejos mecanismos de evolución; el objetivo de la investigación fue obtener información para realizar un mejor abordaje clínico-terapéutico de pacientes con este tumor, fueron utilizados 20 perros con diagnóstico clínico y citológico de TVT; fue realizada la estadificación clínica (TNM), la clasificación citomorfológica y la descripción de criterios de malignidad nuclear y citoplasmáticos. Para el análisis de los datos se utilizaron los test estadístico chi-cuadrado y el Mann-Whitney. 18 animales eran mestizos con un rango de edad entre los 2 a 10 años, la principal localización del tumor fue a nivel genital externo y el tipo celular más común fue el plasmocitóide; los criterios de malignidad nucleares y citoplasmáticos con excepción del halo perinuclear fueron similares a los descritos en la literatura. Durante la clasificación TNM, fueron categorizados dos tumores en estado T3M y uno en T3N1, los demás en diferentes grados de T. A pesar de la ausencia de significancia estadística por el método empleado, en general, fue vista una buena relación clínica entre la estadificación TNM y los hallazgos citopatológicos, lo que sugiriere que ambos son complementarios para proveer mayor seguridad sobre el grado de agresividad, evolución y pronóstico en pacientes con TVT, como sucede con otros tipos de tumores. Emplear esta estadificación en este tumor, puede servir como criterio para decidir una posible evolución y tipo de terapia, sin embargo, como es el primer trabajo en este sentido, recomendamos futuras investigaciones que ayuden a definir las ventajas de utilizar la estadificación clínica TNM en el TVT.
Estadificación clínico y citológico del tumor venéreo transmisible en el hospital veterinario de Botucatu
Keywords: Cytopathology; Dog; Plasmocytoid; Citopatología; Plasmocitóide; Perro